2002
DOI: 10.1097/01.lab.0000017371.72714.c5
|View full text |Cite
|
Sign up to set email alerts
|

Common Adult Stem Cells in the Human Breast Give Rise to Glandular and Myoepithelial Cell Lineages: A New Cell Biological Concept

Abstract: SUMMARY:Breast biology and pathology are currently shaped by the two-cell concept that recognizes only glandular and myoepithelial cells. In the present study, we have visualized a previously unidentified cell population within the epithelial compartment of the breast, which displays the phenotypic characteristics of a committed stem cell. Immunofluorescence double labeling with digital image processing and Western blotting were applied to normal breast tissue as well as to noninvasive and invasive breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
241
2
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(266 citation statements)
references
References 22 publications
18
241
2
5
Order By: Relevance
“…In solid areas, p63-positive cells were predominant. By classifying breast cell populations according to the system proposed by Bocker, 36 we identified four distinct types of cells in adenoid cystic carcinoma of the breast; rare CK5/6 þ cells (CK8/18À/p63À) or progenitor cells, CK5/6 þ /CK8/18 þ cells (/p63À) or glandular precursor cells, CK8/18 þ cells Although the origin of adenoid cystic carcinoma of the breast is still debated, it seems to be widely accepted that this tumor is derived from undifferentiated cells, which have the capacity to differentiate towards ductal and myoepithelial cells. 9,10,25,37 Our study confirmed this theory, as we demonstrated the presence of CK5/6 þ cells that could represent precursor cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In solid areas, p63-positive cells were predominant. By classifying breast cell populations according to the system proposed by Bocker, 36 we identified four distinct types of cells in adenoid cystic carcinoma of the breast; rare CK5/6 þ cells (CK8/18À/p63À) or progenitor cells, CK5/6 þ /CK8/18 þ cells (/p63À) or glandular precursor cells, CK8/18 þ cells Although the origin of adenoid cystic carcinoma of the breast is still debated, it seems to be widely accepted that this tumor is derived from undifferentiated cells, which have the capacity to differentiate towards ductal and myoepithelial cells. 9,10,25,37 Our study confirmed this theory, as we demonstrated the presence of CK5/6 þ cells that could represent precursor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsentinel axillary lymph node dissection was performed in Adenoid cystic carcinoma of the breast S Azoulay et al eight cases. The median number of lymph nodes examined was 12 (range: [7][8][9][10][11][12][13][14][15][16][17][18][19]. No lymph node metastases were seen in either of these cases.…”
Section: Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both glands contain K5/K14/p63-positive progenitor cells, which give rise to glandular cells with subsequent downregulation of basal keratins/p63 and upregulation of glandular keratins K7/K8/18. Furthermore, it has been demonstrated for breast tissue that the myoepithelial cells originate (embryologically, in transplantation studies, and during physiological regeneration) from K5 and/or K14-positive progenitors 52,53,55 that co-express p63. 16 Our isTILT data provide support for similar cellular differentiation processes in the salivary gland (Boecker et al, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…Many markers have been postulated to identify breast stem/progenitor cells in both the luminal and myoepithelial compartments. [20][21][22][23][24][25][26] Our experience with one of these putative stem cell markers, CK5/6, 21 is that its expression in normal breast is typically seen in a continuous portion of the basal epithelial compartment, suggesting a myoepithelial expression phenotype. Other authors have provided some evidence that CK5/6 reactivity may not, indeed, represent a stem cell phenotype.…”
Section: Discussionmentioning
confidence: 99%